Mohammedan Mosque, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
Photo of mosque in Port of Spain, Trinidad and Tobago. Handwritten letter from Ella to Mr. and Mrs. A.S. Wilkinson. 6 cents Trinidad and Tobago stamp. Photo no. 13. Postcard number 77767.
Colour: White, Green, Brown, Red, Blue and Cream Hues; Style: Landscape; Other: Bordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Mosques--Trinidad and Tobago; Islam--Trinidad and Tobago; Muslims--Trinidad and Tobago; Architecture--Trinidad and Tobago; 1948; Architecture, Asian--Trinidad and Tobago; Islamic architecture--Trinidad and Tobago; Minarets--Trinidad and Tobago